English English - Rahmadhani, An Nisa Fitri; Adrallisman (Fakultas Sosial dan Humaniora - Universitas Buddhi Dharma, 2025)
This research presents an analysis of the anxiety experiences of Connell Waldron from the 266-page novel Normal People by Sally Rooney first published in 2018 by Faber & Faber. Normal People is a novel that tells a story about two people’s relationships and lives. Connell Waldron, one of the main characters, suffers from anxiety that affects his behavior and actions, especially in his relationships. This research studies the anxiety experienced by Connell based on the anxiety theory from the psychoanalysis collection theories by Freud that consists of three types of anxiety which are reality anxiety, neurotic anxiety, and moral anxiety. This research uses qualitative methods to study the character Connell based on all three types of anxiety by Freud. The data is collected from dialogues and narrations from the novel and analyzed and discussed to get the research findings. The writer found that Connell experiences all of the three anxiety types. The results show that Connell’s anxiety stems from external dangers like financial crises, internal psychological issues, and guilt from violating social expectations and morals.